The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s43593-022-00012-4
|View full text |Cite
|
Sign up to set email alerts
|

Computational imaging without a computer: seeing through random diffusers at the speed of light

Abstract: Imaging through diffusers presents a challenging problem with various digital image reconstruction solutions demonstrated to date using computers. Here, we present a computer-free, all-optical image reconstruction method to see through random diffusers at the speed of light. Using deep learning, a set of transmissive diffractive surfaces are trained to all-optically reconstruct images of arbitrary objects that are completely covered by unknown, random phase diffusers. After the training stage, which is a one-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 91 publications
0
72
0
Order By: Relevance
“…Some of these errors can be mitigated by selecting appropriate fabrication methods, e.g., high-precision lithography, and using less absorptive materials. Moreover, our previous results 23 , 38 , 44 , 49 , 50 showed that some of these uncontrolled physical errors and imperfections did not lead to a significant discrepancy between the experimental and numerical, expected results, indicating the correctness of the assumptions involved in our optical forward model and training procedures. Even if these errors and imperfections become considerable, the performance degradation of a diffractive network caused by some of these experimental factors can be compensated by incorporating them as random variables into the physical forward model of the diffractive network during the training process.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Some of these errors can be mitigated by selecting appropriate fabrication methods, e.g., high-precision lithography, and using less absorptive materials. Moreover, our previous results 23 , 38 , 44 , 49 , 50 showed that some of these uncontrolled physical errors and imperfections did not lead to a significant discrepancy between the experimental and numerical, expected results, indicating the correctness of the assumptions involved in our optical forward model and training procedures. Even if these errors and imperfections become considerable, the performance degradation of a diffractive network caused by some of these experimental factors can be compensated by incorporating them as random variables into the physical forward model of the diffractive network during the training process.…”
Section: Discussionmentioning
confidence: 61%
“…Motivated by the massive success of artificial intelligence and deep learning, in specific, a myriad of new hardware designs for optical computing have been reported recently, including, e.g., on-chip integrated photonic circuits 16 22 , free-space optical platforms 23 28 , and others 29 31 . Among these different optical computing systems, the integration of successive transmissive diffractive layers (forming an optical network) has been demonstrated for optical information processing, such as object classification 23 , 32 – 43 , image reconstruction 38 , 44 , all-optical phase recovery and quantitative phase imaging 45 , and logic operations 46 – 48 . A diffractive network is trained using deep learning and error-backpropagation methods implemented in a digital computer, after which the resulting transmissive layers are fabricated to form a physical network that computes based on the diffraction of the input light through these spatially-engineered transmissive layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stark contrast, spatial analog computing modulates incident wavefronts in real space, enabling massive and high-throughput parallel operations for required signal-processing tasks such as spatial differentiation 8 10 , integration 11 and solving equations 12 , 13 . Conventional physical architectures of spatial domain analog computers leverage upon the phase accumulation with stacked or series of optical elements 14 , 15 , making the whole system bulky and lossy. Nevertheless, metasurface has been captivated as a popular notion and a promising candidate for highly efficient, compact and ultrathin analog processors 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…By combining novel deep neural network (DNN) architectures and domain knowledge in optical physics, the performance limits in various systems are continuously being re-defined, including spatial resolution 3 , 4 , depth-of-field 5 , space-bandwidth product 6 , imaging speed 6 , 7 , sensitivity to low-photon count 8 , and resilience to random scattering 9 , 10 . Of particular interest by Luo et al 11 is the ability to overcome random scattering by a DNN.…”
mentioning
confidence: 99%